Bioethics knowledge, attitudes, and practices among healthcare professionals in Cameroon: a cross sectional analytical observational study of doctors and nurses in Cameroon’s Southwest Region - Kevin T. J. Dzi; Oscaline N. Ndong; Elisabeth Z. Menkem; Nicholas Tendongfor (Discover Public Health)
Abstract Knowledge of bioethics could assist healthcare professionals in working ethically, thus enhancing the quality of patient care. We conducted a study to assess physicians' and nurses' knowledge, attitudes, and behaviours regarding healthcare ethics in Cameroon's southwest region. 469 healthcare professionals were recruited, with 89.8% being nurses and 10.2% being doctors. Women made up 79.6% of nurses, while men made up 60.4% of physicians. The percentage of healthcare professionals who demonstrated good knowledge regarding the most commonly applied biomedical ethics principles varied from 62.9 to 73.1%. There were significant differences in agreement levels between doctors and nurses on statements such as physician-assisted suicide, physicians not refusing to assist with abortions if the law allowed it, and seeking informed consent only for operations and not tests. Nurses were three times more likely to agree with the statements that doctors cannot refuse abortion if the law allows it and that patients who want assisted suicide should be assisted to get it. Most healthcare providers were found to consistently adhere to healthcare ethics in their practices. However, there was a significant difference in opinion between doctors and nurses when asked if they ordered tests that were not medically necessary but were ordered for patient satisfaction, with nurses having a lower likelihood of agreeing to such practices than doctors. While participants demonstrated a moderate knowledge of healthcare ethics, additional educational interventions are needed to cultivate more favourable attitudes toward specific aspects of healthcare ethics, such as informed consent, patient autonomy, paternalism, and confidentiality.